Familial SYN1 variants related neurodevelopmental disorders in Asian pediatric patients - Juan Xiong; Haolin Duan; Shimeng Chen; Miriam Kessi; Fang He; Xiaolu Deng; Ciliu Zhang; Li Yang; Jing Peng; Fei Yin (BMC, 2021)
Abstract Background SYN1 encodes synapsin I, which is a neuronal phosphoprotein involving in regulating axonogenesis and synaptogenesis. Variants in the gene have been associated with X-linked neurodevelopmental disorders in recent years. Methods In the study, we reported two male patients with familial SYN1 variants related neurodevelopmental disorders from Asian population. Previously published cases with significant SYN1 variants from the literature were also included to analyze the phenotype and genotype of the disorder. Results Two maternally inherited SYN1 variants, including c.C1076A, p.T359K in proband A and c.C1444T, p. Q482X in proband B (NM_133499) were found, which have never been described in detail. Combining with our research, all reported probands were male in the condition, whose significant SYN1 variants were inherited from their asymptomatic or mild affected mother. Although the disorder encompasses three main clinical presentations: mental deficiency, easily controlled reflex seizure and behavior problems, patients' clinical manifestations vary in genders and individuals, even in the same pedigree. Conclusion We firstly reported two familial SYN1-related neurodevelopmental disorders in Asian pediatric patients. Gender and phenotype differences should be highly valued in the disorder.